Yb3+ sensitized Na2Y2B2O7:Er3+ phosphors in enhanced frequency upconversion, temperature sensing and field emission display. (May 2017) - Soni, Abhishek Kumar; Rai, Vineet Kumar; Mahata, Manoj Kumar
Graphical abstract: Schematic representation for the applications of Na2Y2B2O7:Er 3+ /Yb 3+ phosphors in various fields. Highlights: Na2 Y2 B2 O7 :Er 3+ /Yb 3+ phosphors with single monoclinic phase have been synthesized. FIR investigations have been carried out in the green UC emission bands. The UC intensity for the green band has been enhanced about ∼1433 times. The maximum sensitivity 7.9 × 10 −3  K −1 at 300 K has been reported. The phosphors exhibit intense green emission upon electron beam excitation. Abstract: Na2 Y2 B2 O7 :Er 3+ /Yb 3+ crystalline phosphors with single monoclinic phase have been synthesized by urea assisted solution combustion method and characterized through X-ray diffraction and Field emission scanning electron microscopy analysis. Frequency upconversion (UC) emission study has been carried out upon 980 nm laser diode excitation and maximum enhancement of about ∼1433 times for the UC emission intensity of the green band in the codoped phosphor compared to that of the singly Er 3+ doped phosphor has been reported. Optical temperature sensing study performed in the developed codoped phosphor reveals that the material can be used temperature sensing application within 300–613 K temperature range with maximum sensitivity ∼7.9 × 10 −3  K −1 at 300 K. The low-voltage cathodoluminescence measurements have been performed for Na2 Y2 B2 O7 :Er 3+ -Yb 3+ phosphors as a function of accelerating voltage and filament current. The developed phosphors exhibit highly intense green emission with some weak emission bands in violet, blue and red regions upon electron beam excitation.